Abba Abraham Buruk Woldegaber and Mario Alexis Portella, Abyssinian Christianity, the First Christian Nation? The History and the Identity of the Ethiopian and Eritrean Christians - Ancel, Stéphane (Aethiopica, 2017)
Review